Effects of trade and technology on the Mexican labor market - Gabriela López Nori (Banco de México, 2021)
This paper assesses the effects of trade and technological change on Mexico's labor market between 1994 and 2019. The implications of the exposure of local labor markets to greater trade integration under NAFTA and to greater competition from China in the US market are analyzed, as are the consequences of the exposure of local labor markets to automation. The main results show that trade integration under NAFTA promoted employment in Mexico for all demographic groups, especially for women and the less educated. In addition, it is also found that trade integration reduced unemployment and the non-participation rate. China's competition in the US market had the opposite effects on these indicators. Finally, the analysis by sector (manufacturing and non-manufacturing) suggests that those markets susceptible to automation experienced a pattern of labor polarization.
Keywords: F13; F16; O33; 330; Trade Policy; Labor Markets; Technology Adoption; Technology and Employment